2021
DOI: 10.3233/jad-200959
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging

Abstract: Background: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. Objective: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. Methods: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…The comparison group, MCSA participants without TJA, do not necessarily represent how patients with TJA might have fared without the procedure, especially because higher levels of physical activity are associated with less pronounced cognitive decline. 38 Blood metal measurements were not available because they were rarely measured clinically. We did not have information on TJA failure modes.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison group, MCSA participants without TJA, do not necessarily represent how patients with TJA might have fared without the procedure, especially because higher levels of physical activity are associated with less pronounced cognitive decline. 38 Blood metal measurements were not available because they were rarely measured clinically. We did not have information on TJA failure modes.…”
Section: Discussionmentioning
confidence: 99%
“…We and other researchers have shown that substituting SB with MVPA mathematically improves lower limb strength and function among aged persons. They may remain reluctant to perform higher intensity physical activity as suggested [30,31], considering that in an aging society, older adults are often afflicted with comorbidities or functional decline [32]. Importantly, our findings on substituting SB with LPA, which was positively associated with upper limb strength and lower limb function, may pave the way for designing a feasible regimen of combined LPA and MVPA in varying proportions for older adults.…”
Section: Discussionmentioning
confidence: 86%
“…By analyzing the data obtained from 864 community-dwelling older adults from the Suwon Geriatric Mental Health Center, the work of Kim et al [ 13 ] showed that PA positively contributed to cognitive function, perhaps via anti-depressant effects, in study subjects. Additionally, findings from the Longitudinal Ageing Study in India [ 14 ], French tri-city research [ 15 ], and the Mayo Clinic Study of Aging [ 40 ] also recognize the cognitive benefits of PA among community-dwelling older adults. Taken together, the findings from the current and previous studies support the cognitive benefits of PA later in life.…”
Section: Discussionmentioning
confidence: 99%